Child Rights Education in Law No. 35 of 2014 on Child Protection - Zuhroh, Diana; Aziz, Abdul (Universitas Negeri Semarang, 2024)
Protection of children and their rights is the domain of all groups, including parents, students, educators, regional governments, central government and other parties. The role of the State is also urgently needed to formulate regulations that regulate the protection of children's rights from various negative actions that make children victims and protect children as perpetrators of crimes. One of the regulations currently in effect is Law No. 35 of 2014 concerning Child Protection. This law must be interpreted as a guideline for all parties so as not to violate children's rights. However, children must also know and be aware of their rights and the protection of these rights. Massive education must be carried out throughout society, including schools or Islamic boarding schools. This community service activity aims to determine the level of understanding of students at Darul Quran Science High School Colomadu Karanganyar regarding Law No. 35 of 2014 concerning Child Protection before community service activities are carried out and how students understand it after the child rights education program in Law No. 35 of 2014 concerning Child Protection. This community service activity uses an interactive method, where the resource persons provide socialization and understanding of the contents of Law No. 35 of 2014 concerning Child Protection to students, and the resource persons provide opportunities for students to ask questions. The resource person then asked questions related to the material that had been presented to the students and the students answered them. The results of the activity show that students do not know Law No. 35 of 2014 concerning Child Protection and its material. However, after the resource person explained the various rights of children in law, protection for children in the event that children become victims and perpetrators of crimes, state instruments that provide protection for children and so on, the students understood the material presented by the resource person. This can be seen from students' understanding of the questions asked by the resource person regarding the material that has been presented previously.